The impact of capital structure on profitability: focusing on automotive parts industry on Malaysian firms / Nur Amanina Azra'ai - Azra'ai, Nur Amanina (2016)
The purpose of this paper is to investigate the impact of capital structure on firm profitability. Multiple regression analysis is used in the study in estimating the relationship between the capital structure and firm's performance. Based on a sample of eleven manufacturing firms in automotive parts industry that listed in Bursa Malaysia from 2006 to 2015, the results indicate that interest coverage and asset tangibility are significantly and positively effect to firm performance measured by ROA, while report a negative relation between total debt, short term debt, long term debt and total capital with firm performance, ROA.